If x - 4 , x + 2 and 3x + 6 form a geometric sequence, find x.
1 answer:
Answer:
x =7
Step-by-step explanation:
Remark
- A geometric sequence always has terms that are separated by a common ratio. For example 3 9 27 81 243 ....
- Each term is multiplied by a common number and the term before it. In this case the common term is 3.
- To get the next term after 9, you multiply 9 by 3.
- To get the common ratio divide the second term by the first and then the third term by the second
Equation
(x + 2)/(x - 4) = (3x + 6)/ (x + 2)
Solution
I would begin this problem by taking out the common factor on the top right term. You'll see why in a second.
(x + 2)/(x - 4) = 3(x + 2)/ (x + 2) Notice the two binomials on the right cancel.
- (x + 2)/(x - 4) = 3/1 Cross multiply
- (x + 2)*1 = 3*(x - 4) Remove the brackets on the right.
- x + 2 = 3x - 12 Add 12 on both sides.
- x + 2 + 12 = 3x - 12 + 12 Simplify
- x + 14 = 3x Subtract x from both sides
- 14 = 3x - x
- 2x = 14 Divide by 2
- x = 14/2
- x = 7
You might be interested in
Answer: 4
Step-by-step explanation: :)
Answer:
12 units
Step-by-step explanation:
Because the two triangles are similar:
Hope this helps!
√7 is not a perfect square , so it's irrational
Answer is B. irrational numbers
P.S .
Keep in mind that any of non perfect square is irrational
Answer: Choice B) -5.2 degrees
=====================
Work Shown:
Add up the given temperatures
-42 + (-17) + 14 + (-4) + 23 = -26
Then divide by 5 since there are 5 values we're given
-26/5 = -5.2
Here you go hope this helps